2008
DOI: 10.1104/pp.107.112946
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Chloroplast DNA Molecules and the Effects of Light on the Amount of Chloroplast DNA during Development in Medicago truncatula      

Abstract: We used pulsed-field gel electrophoresis and restriction fragment mapping to analyze the structure of Medicago truncatula chloroplast DNA (cpDNA). We find most cpDNA in genome-sized linear molecules, head-to-tail genomic concatemers, and complex branched forms with ends at defined sites rather than at random sites as expected from broken circles. Our data suggest that cpDNA replication is initiated predominantly on linear DNA molecules with one of five possible ends serving as putative origins of replication. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 32 publications
3
39
0
1
Order By: Relevance
“…We classified the chloroplasts into three types with respect to DAPI-DNA signal and then scored the number of cells (Supplemental Figure 2; see Methods), protoplasts, and isolated chloroplasts in each category (Table 1). These results demonstrate that plastids without detectable DAPI-DNA are present in the mature leaf blade and indicate that our inability to detect punctate forms of ptDNA in some chloroplasts cytologically is not attributable to a DNase artifact, as suggested by Golczyk et al, but to a decrease in ptDNA content and/or molecular integrity as leaves develop, as we concluded previously Rowan et al, 2004Oldenburg et al, 2006;Shaver et al, 2006Shaver et al, , 2008Zheng et al, 2011). This progression of proplastid-to-chloroplast development is shown in Supplemental Figure 3, illustrating a visible reduction in DAPI-DNA intensity and decreased genome equivalents per plastid for the mature chloroplasts (Table 2).…”
Section: Dapi-dna In Maize Tissue Sections Protoplasts and Isolatedsupporting
confidence: 86%
See 2 more Smart Citations
“…We classified the chloroplasts into three types with respect to DAPI-DNA signal and then scored the number of cells (Supplemental Figure 2; see Methods), protoplasts, and isolated chloroplasts in each category (Table 1). These results demonstrate that plastids without detectable DAPI-DNA are present in the mature leaf blade and indicate that our inability to detect punctate forms of ptDNA in some chloroplasts cytologically is not attributable to a DNase artifact, as suggested by Golczyk et al, but to a decrease in ptDNA content and/or molecular integrity as leaves develop, as we concluded previously Rowan et al, 2004Oldenburg et al, 2006;Shaver et al, 2006Shaver et al, , 2008Zheng et al, 2011). This progression of proplastid-to-chloroplast development is shown in Supplemental Figure 3, illustrating a visible reduction in DAPI-DNA intensity and decreased genome equivalents per plastid for the mature chloroplasts (Table 2).…”
Section: Dapi-dna In Maize Tissue Sections Protoplasts and Isolatedsupporting
confidence: 86%
“…(Reprinted from Rowan and Bendich [2009], Figure 1. ) to pale-green chloroplast to fully green chloroplast (as well as the etioplast-tochloroplast transition upon illumination of etiolated maize seedlings) Rowan et al, 2004Oldenburg et al, 2006;Shaver et al, 2006Shaver et al, , 2008Zheng et al, 2011). Those data (summarized in Figure 1) show that after the decrease to the level in mature chloroplasts, ptDNA remains essentially constant as leaves reach maturity, in agreement with the conclusion of Golczyk et al As for gerontoplasts in senescing leaves, although Golczyk et al concluded that the ptDNA level remains unchanged, their description may, in fact, reflect a decline in ptDNA, as they noted that "DNA fluorescence became more and more diffuse and difficult to visualize."…”
Section: Quantitative Conclusion From Nonquantitative Datamentioning
confidence: 99%
See 1 more Smart Citation
“…SHAVER et al (2008) verificaram que modulações na fluência de luz azul alteram a estrutura e as taxas de degradação de DNAs cloroplastídicos e a divisão plastídica em Medicago truncatula.…”
Section: Introductionunclassified
“…Chloroplasts also contain multiple copies of DNA (approximately 1,000 copies; Boffey and Leech, 1982;Miyamura et al, 1986;Baumgartner et al, 1989;Oldenburg and Bendich, 2004;Oldenburg et al, 2006;Shaver et al, 2008). In algae, chloroplast DNA is replicated in a manner that keeps pace with chloroplast and cell division in order to maintain the proper DNA content per chloroplast (i.e.…”
mentioning
confidence: 99%